Analisis Pengelolaan Sampah Pada Masyarakat Desa Tanjung Rejo, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang Sumatera Utara - Mardiana Lestari Siahaan; Meutia Nanda; Bachtiar Shaleh Simbolon; Mawaddah; Rismaya Rismaya; Sabillah Sabillah; Yolanda Fidorova (Universitas Widya Gama Mahakam Samarinda, 2023)
Waste is an actual problem for a long time for the Indonesian state, especially for urban areas due to the influence of the social, cultural and economic conditions of the local community. This research was conducted in the working area of the Tanjung Rejo Health Center, Tanjung Rejo village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The results of the observation and distribution of 100 questionnaires to the community with an overall research sample were women, more precisely a housewife (IRT) in Tanjung Rejo Village as many as 100 respondents processed waste by burning, because the village did not cooperate with the local government cleaning office.